Micro-Magnetic Activity of the Fabricated MnFe2O4 via Co-Precipitation from Natural Iron Sand - Rianna, Martha; Hussain, Muhammad Khalid; Sembiring, Timbangen; Guk-Guk, Herwati Permata Indah Raja; Sitorus, Kurnia Jesiska; Setiadi, Eko Arief; Tetuko, Anggito P.; Sebayang, Perdamean (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study explores the micromagnetic behaviour of MnFe2O4 derived from natural iron sand through the coprecipitation method, without the need for calcination. Using manganese chlo-ride and iron sand as precursors, one can create MnFe2O4. Through the utilisation of X-ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX), and Vibrating Sample Magnetometer (VSM), one can effectively analyse and understand the crystal structure, morphology, and magnetic properties. The crystal size was reduced by a fac-tor of 0.40 nm, as revealed by XRD crystal structure analysis. Additionally, the XRD results indicated the absence of impurities, confirming the presence of a single phase. In addition, the SEM analysis revealed that samples 1, 2, and 3 underwent agglomeration. The particles have a cubic shape. The analysis using EDX indicates that there are no other elements present in the Mn, Fe, and O. Additionally, the VSM analysis confirms that the sample exhibits magnetic hardness. Sample 1 exhibits exceptional magnetic properties, with Ms values of 217.53 emu/g, Mr 34.27 emu/g, and Hc 127.42 emu/g. Photoluminescence (PL) spectroscopy was used to observe the optical properties of MnFe2O4. Sample 1 exhibits a distinct emission spectrum at 440 nm, representing the purple band. Sample 2 displays a sharp emission spectrum at 448 nm, indicating the blue band. Lastly, Sample 3 demonstrates a clear emission spectrum at 427 nm, signifying the purple band.